Statistical methods in practice - for scientists and technologists - Boddy, Richard (Wiley, 2009)
"This book presents a broad range of methods which form the core of a statistical toolkit required by scientists and technologists, including descriptive statistics (e.g. mean, median, standard deviation), inference (confidence intervals), significance testing for one mean, two means, two standard deviations, distributions (Normal, Binomial, Poisson), exploratory data analysis (box plots), nonparametric methods, regression and correlation, cusum charts for plotting data over time and detecting changesA hands-on, practical approach to statistics for those with little background in the subject Introduces a broad range of methods which form the core of a statistical toolkit required by scientists and technologists, presented from descriptive statistics to nonparametric methods Includes a supporting website, providing software to aid tutorials Based on practical courses given to scientists and technologists of all levels Combines realistic case studies and examples with a practical approach to statistical analysis"--[Résumé de l'éditeur].